2021
DOI: 10.1155/2021/7407086
|View full text |Cite|
|
Sign up to set email alerts
|

miR-486 Promotes the Invasion and Cell Cycle Progression of Ovarian Cancer Cells by Targeting CADM1

Abstract: Objective. To explore the role and possible underlying mechanism of miR-486 in ovarian cancer (OC) cells. Methods. The expression of miR-486 and CADM1 was detected by qRT-PCR in OC tissues and adjacent nontumor tissues and OC cell lines. The dual-luciferase reporter gene system was used to determine the targeting relationship between miR-486 and CADM1. CCK-8, colony formation assay, Transwell, and flow cytometry were performed to detect cell proliferation, cell invasion, cell cycle progression, and the apoptot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Xiong et al 26 showed that XIST can act on miR‐486‐5p to regulate brain ischemia–reperfusion injury. In addition, miR‐486 could participate in the biological functions of ovarian cancer cells by interacting with CADM1 in an ovarian cancer study 27 . Based on our network, XIST/circRNA_2773‐miR‐486‐5p‐CADM1 and other related pathways involved in the occurrence and development of AF, the down‐regulated XIST, circRNA_2773, and CADM1 were negatively correlated with miR‐486‐5p expression and had a targeting relationship with miR‐486‐5p.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Xiong et al 26 showed that XIST can act on miR‐486‐5p to regulate brain ischemia–reperfusion injury. In addition, miR‐486 could participate in the biological functions of ovarian cancer cells by interacting with CADM1 in an ovarian cancer study 27 . Based on our network, XIST/circRNA_2773‐miR‐486‐5p‐CADM1 and other related pathways involved in the occurrence and development of AF, the down‐regulated XIST, circRNA_2773, and CADM1 were negatively correlated with miR‐486‐5p expression and had a targeting relationship with miR‐486‐5p.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, miR‐486 could participate in the biological functions of ovarian cancer cells by interacting with CADM1 in an ovarian cancer study. 27 Based on our network, XIST/circRNA_2773‐miR‐486‐5p‐CADM1 and other related pathways involved in the occurrence and development of AF, the down‐regulated XIST, circRNA_2773, and CADM1 were negatively correlated with miR‐486‐5p expression and had a targeting relationship with miR‐486‐5p. That is, XIST/circRNA_2773 could competitively bind miR‐486‐5p to act as a “sponge,” thus diminishing the inhibitory effect of miR‐486‐5p on CADM1.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…At present, large number of DNMT inhibitor candidates which can inhibit DNA methylation are in the developmental pipeline and some are currently in clinical trials ( 49 ). Although there is no study on increasing the expression of CADM1 through regulating associated miRNAs in PTC up to now, there are some studies on other cancers: inhibiting microRNA-1246 can increase the expression of CADM1 in hepatocellular carcinoma ( 50 ); upregulating miR-486 can downregulate CADM1 expression in Ovarian Cancer ( 51 ); miR-155-3p could downregulate expression of CADM1 in breast cancer ( 33 ). Thus, more researches are needed to explore related miRNAs in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…They further found that inhibiting the miRNA not only increased the expression of CADM1 but inhibited activation of the STAT3 pathway, a determinant of GBM proliferation and tumorgenicity. A similar study in ovarian cancer cells described the downregulation of the CADM1-targeting miR-486, which saw reduced cell viability, proliferation, and an increased proportion of cells in G0/G1 arrest [ 49 ]. Moreover, CADM1 was inversely proportional to the expression of cyclin D1, cyclin E, CDK6, and p21.…”
Section: Discussionmentioning
confidence: 99%